2013
DOI: 10.3389/fnins.2013.00014
|View full text |Cite
|
Sign up to set email alerts
|

An FPGA Implementation of a Polychronous Spiking Neural Network with Delay Adaptation

Abstract: We present an FPGA implementation of a re-configurable, polychronous spiking neural network with a large capacity for spatial-temporal patterns. The proposed neural network generates delay paths de novo, so that only connections that actually appear in the training patterns will be created. This allows the proposed network to use all the axons (variables) to store information. Spike Timing Dependent Delay Plasticity is used to fine-tune and add dynamics to the network. We use a time multiplexing approach allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 24 publications
1
52
0
Order By: Relevance
“…The experimental results showed that the CETC model requires reduced hardware resources and accurately reproduces the thalamocortical dynamical characteristics in both the normal and Parkinsonian states. Numerous studies have proposed FPGA-based implementation of the realistic neural networks with different hardware structures and methods for the real-time emulations of the large-scale networks46474849. The real-time emulations of the large-scale neural networks are of vital significance to understand how the brain transfers, decodes and processes information5051.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results showed that the CETC model requires reduced hardware resources and accurately reproduces the thalamocortical dynamical characteristics in both the normal and Parkinsonian states. Numerous studies have proposed FPGA-based implementation of the realistic neural networks with different hardware structures and methods for the real-time emulations of the large-scale networks46474849. The real-time emulations of the large-scale neural networks are of vital significance to understand how the brain transfers, decodes and processes information5051.…”
Section: Discussionmentioning
confidence: 99%
“…. , t 0 ) does depend on t 0 (the second term in (28)) and this dependence cannot be eliminated. See also Appendix, below, where the above general reasoning is illustrated for the LIF neuronal model with threshold 2 (that is two input impulses applied in a short succession are able to trigger, see (31), below).…”
Section: Thismentioning
confidence: 99%
“…where [ ] is a random binary variable, is the probability that [ ] = 1, % is the modulo operation and ( [ ]/( + 1)) is the integer part of [ ]/( + 1). The expected value of X is given by (8), and simply represents the fractional part of [ ]/( + 1). The expected value for the decay is thus the integer plus fractional part of [ ]/( + 1) and thus equal to the IIR decay in (3), but we now only need to store a few bits for V[t].…”
Section: B Stochastic Decaymentioning
confidence: 99%